Important Food Sources of Fructose-Containing Sugars and Blood Pressure: A Systematic Review and Meta-Analysis of Controlled Trials. (7th June 2021) - Liu, Qi; Chiavaroli, Laura; Ayoub-Charette, Sabrina; Khan, Tauseef; Au-Yeung, Fei; Cheung, Annette; Lee, Danielle; Ahmed, Amna; Mejia, Sonia Blanco; de Souza, Russell J; Wolever, Thomas; Leiter, Lawrence; et al.
Abstract: Objectives: Overconsumption of fructose-containing sugars may increase blood pressure. Whether this effect is mediated by the food matrix is unclear. We conducted a systematic review and meta-analysis of controlled feeding trials of the effect of food sources of fructose-containing sugars at different levels of energy control on blood pressure (NCT02716870). Methods: We searched MEDLINE, Embase and the Cochrane Library through January, 2020 for controlled trials ≥7d. Trial designs were prespecified based on energy control: substitution (energy matched replacement of sugars in the diet); addition (excess energy from sugars added to diets); subtraction (energy from sugars subtracted from diets); and ad libitum (energy from sugars freely replaced in the diet) trials. Outcomes were systolic blood pressure (SBP) and diastolic blood pressure (DBP). Independent reviewers extracted data and assessed risk of bias. Certainty of evidence was assessed by GRADE. Results: We included 76 trials (121 trial comparisons, N = 4 302) assessing 9 food sources (sugar-sweetened beverages [SSBs], sweetened dairy alternatives, 100% fruit juice, fruit, dried fruit, sweets, added nutritive sweetener, sweetened cereal grains/bars, and mixed sources) across the 4 levels of energy control. Total fructose-containing sugars decreased SBP (mean difference, −2.76 mmHg [95% CI, −4.36, −1.16], P = 0.001) and DBP (−1.26 mmHg [−2.29, −0.23], P = 0.016) in addition trials and the removal of these sugars decreased SBP (−1.79 mmHg [−3.36, −0.21], P = 0.026) in subtraction trials. There was evidence of interaction by food source with fruit decreasing and sweets and mixed sources increasing SBP and DBP in addition trials and the removal of SSBs decreased SBP in subtraction trials. The certainty of evidence was generally moderate to low for all food source-outcome relationships, except for the decreasing-effect of fruit on DBP in addition trials (high). Conclusions: Food source and energy control appear to mediate the effect of fructose-containing sugars on blood pressure. The evidence provides a good indication that fruit decreases while excess calories from SSBs, sweets and mixed sources increase blood pressure. More high-quality trials of different food sources are needed to improve our estimates. Funding Sources: Diabetes Canada.